Optimizing QoS in LEO Satellite Networks: A Review of Handoff Algorithms and Satellite Diversity Strategies - Sharma, Rubal; Malik, Sangeeta (Journal of Global Economy, Business and Finance, 2026)
Any robust communication system can be defined as one that can provide ubiquitous connectivity with lower latency periods. Since 1990, Low Earth Orbit (LEO) satellite constellations have proven to be plausible and efficient alternatives to high altitude GEO satellites in delivering seamless voice and data communication services. This is due to some of their important advantages over geo- stationary such as low power requirement, efficient utilization of frequency spectrum and, low propagation delays pertaining to the satellite’s closer proximity to the ground station. On the downside, the difference in the mobility speed of a LEO satellite and a user on earth is so high that the user can be considered constant, unless he/she is on a fast-moving vehicle. This calls for strategical user handover mechanisms between LEOs to avoid call drops, as usually the service time for a user tend to be higher than the coverage time of a typical non-stationary LEO. Consequently, it is admissible to claim that the quality of service provided by such a network is limited by the performance of LEO handoff algorithms (generally based on parameters like Probability of call blocking/call termination, Throughput, Delay in transmission). In this paper, we will discuss the LEO handoff algorithms developed over the years and particularly delve into the most commendable satellite handover techniques exploiting the property of satellite diversity, that fall with Acceptable Forced termination of existing calls and dropping of new calls.